Breast Cancer Survival Defined by Biological Receptor and Menopausal Status in Vietnamese Women. (23rd July 2019) - Vu Hong, Thang; Nguyen Ba, Duc; Skoog, Lambert; Ta Thanh, Van; Tani, Edneia
Little is known about breast cancer in Vietnamese women. Previous studies have reported the frequencies of prognostic factors of breast cancer in this population. The aim of this study was to examine the prognostic factors associated with the survival rates of patients with breast cancer treated at the National Cancer Hospital, Hanoi, Vietnam. We recruited 248 women with operable breast cancer treated with surgery and adjuvant therapy. Tumor tissue samples were stained by many immunohistochemical approaches and analyzed for estrogen receptor, progesterone receptor, and HER2 gene amplification status. A Cox model was used to determine the relationship between survival and the prognostic factors. The disease-free survival rate, overall survival rate, and cancer-specific survival rate were 75.8%, 80.6%, and 86.4%, respectively, at 5 years and 62.3%, 68.1%, and 78.9%, respectively, at 10 years. The lung was the most common metastatic site. Women with factors associated with a poor prognosis (eg, advanced clinical stage, high tumor grade, progesterone receptor [PR] negativity, HER2 amplification) had significantly lower survival rates. Patients with PR-negative breast cancer had significantly worse survival rates compared to those who were PR positive, according to multivariate analysis (hazard ratio = 1.77, 95% confidence interval: 1.01-3.11, P = .045); however, there was only a statistically significant difference in postmenopausal patients. The PR was a prognostic factor in postmenopausal women with breast cancer, but not in premenopausal women.